Improvement of the Gap Adjustment in Total Knee Arthroplasty Using the Posterior Condylar Pre-cut Technique - Kaneyama, Ryutaku; Higashi, Hidetaka; Oinuma, Kazuhiro; Miura, Yoko; Tamaki, Tatsuya; Shiratsuchi, Hideaki (The Journal of Knee Surgery, 2019)
To provide adequate gaps for knee extension and flexion during total knee arthroplasty, a femoral component placement decreases the extension gap because the posterior capsule tension increases against the protrusion of the posterior part of the femoral component. We thought that the influence of this component on the extension gap depends on the amount of posterior femoral bone resection and the thickness of the posterior femoral components. We hypothesized that less bone resection and a thinner posterior part of the femoral component might avoid these problems. To verify our hypothesis, a 4-mm posterior condylar pre-cut technique and temporary femoral components that were 8 and 4 mm thick in the distal and posterior parts, respectively, were made using the FINE Total Knee System (Teijin-Nakashima Medical Co., Okayama, Japan). After bone resection, the pre-cut trial component was set to the femur, and the bone and component setting gaps were estimated. Seventy-one patients (98 knees) were investigated. The average bone gaps were 17.2/15.0 mm (extension/flexion, after pre-cut), 18.3/16.3 mm (after soft tissue release), and 8.7/12.2 mm (after pre-cut trial setting). After pre-cut trial setting, the extension gap decreased significantly; the amount was 1.6 mm (0–4 mm) on average (p < 0.0001), whereas a change of 3 mm or more occurred in 15 knees (15.3%), which could be problematic. The degree of these changes after component setting could be reduced by using the posterior femoral condylar pre-cut technique. However, the problem of component setting on the extension gap was not completely resolved. To precisely project the intraoperative gap to the ultimate postoperative gap, a posterior small protrusion device such as a pre-cut trial with the pre-cut technique would be necessary.
Keywords: total knee arthroplasty; gap adjustment; gap change; component gap; pre-cut technique